Small cell‐ versus large cell‐sized metal stent in endoscopic bilateral stent‐in‐stent placement for malignant hilar biliary obstruction. Issue 6 (24th March 2015) - Lee, Jae Min; Lee, Sang Hyub; Chung, Kwang Hyun; Park, Jin Myung; Paik, Woo Hyun; Woo, Sang Myung; Lee, Woo Jin; Ryu, Ji Kon; Kim, Yong‐Tae
<x xml:space="preserve">Abstract</x> Background and Aim Although the large cell‐sized biliary stent facilitates contralateral stent deployment through the mesh of the first metallic stent for stent‐in‐stent (SIS) technique, there are concerns about its vulnerability to tumor ingrowth. The aim of the present study was to compare the clinical outcomes of endoscopic bilateral SIS placement according to the cell size of a self‐expandable metallic stent (SEMS). Methods A total of 58 patients were enrolled who underwent endoscopic bilateral SIS placement of SEMS for malignant hilar biliary obstruction as a result of cholangiocarcinoma or gallbladder cancer. Finally, 43 patients who underwent successful stent insertion were included in the analysis and divided into the small cell‐sized stent (SCS; n = 21) and the large cell‐sized stent (LCS; n = 22) groups. We retrospectively compared comprehensive clinical and laboratory data in both groups. Results There were no significant differences between the two groups in successful drainage (SCS vs LCS, 100% vs 100%, respectively), early complications (38.1% vs 18.2%), late complications (14.3% vs 22.7%), stent occlusion (42.9% vs 45.5%), tumor ingrowth (33.3% vs 45.5%) or overgrowth (9.5% vs 0%). Duration of stent patency and overall survival were not significantly different between the two groups (P = 0.086 and P = 0.320, respectively). Conclusions Endoscopic bilateral SIS placement for malignant hilar biliary obstruction shows no differences in stent patency, survival, complications and clinical course according to the cell size of SEMS.